Reshaping accounting and management control systems : new opportunities from business information systems - Corsi, Katia; Castellano, Nicola Giuseppe; Lamboglia, Rita; Mancini, Daniela (Springer, 2017)
This book examines the relationship between digital innovations on the one hand, and accounting and management information systems on the other. In particular it addresses topics including cloud computing, data mining, XBRL, and digital platforms. It presents an analysis of how new technologies can reshape accounting and management information systems, enhancing their information potentialities and their ability to support decision-making processes, as well as several studies that reveal how managerial information needs can affect and reshape the adoption of digital technologies. Focusing on the four major aspects data management, information system architecture, external and internal reporting, the book offers a valuable resource for CIOs, CFOs and more generally for business managers, as well as for researchers and scholars. It is mainly based on a selection of the best papers - original double blind reviewed contributions - presented at the 2015 Annual Conference of the Italian Chapter of the Association for Information Systems (AIS).
Keywords: Accounting -- Data processing.; Management information systems.; Technological innovations -- Accounting.; Information technology -- Management.; Cloud computing.; elektronické knihy; electronic books